Effect of NPK Fertilizer and Liquid Organic Fertilizer Lamtoro Leaves (Leucaena leucocephala spp. leucocephala) on The Growth of Cayenne Peppers (Capsicum frutescens L.) - Sofian, M.; Raksun, Ahmad; Handayani, Baiq Sri; Zulkifli, Lalu (Jurnal Biologi Tropis, 2025)
One of the many advantages of lamtoro is that, due to its high nutrient content, it may be utilized as organic fertilizer. Utilizing POC can help plants meet their nutritional needs and avoid nutrient shortages. The purpose of this study is to ascertain how applying NPK fertilizer and liquid organic fertilizer derived from lamtoro leaves, both independently and together, affects the growth of chili plants. Five treatments using NPK fertilizer and liquid organic fertilizer derived from lamtoro leaves were employed in this study, which employed a completely randomized design with three replications. The impact of treatments on the growth metrics of cayenne pepper plants was assessed using a two-way anova test. The results showed that the application of liquid organic fertilizer (POC) derived from lamtoro leaves had a substantial effect on the number of leaves, leaf area, fresh weight, and dry weight. When NPK fertilizer was applied, plant height, leaf count, leaf area, fresh weight, and dry weight all increased. The application of a mixture of liquid organic fertilizer derived from lamtoro leaves and NPK fertilizer did not significantly affect the cayenne pepper plants' fresh weight, dry weight, number of leaves, leaf area, or plant height.